Adenomatous hyperplastic intratracheal ectopic thyroid tissue: a case report. Issue 11 (November 2020) - Liu, Shiyang; Wang, Wanju; Zhao, Lu; Wang, Kun; Xu, Jing; Jiao, Bo; Liu, Chenguang; Zhang, Lin
Intratracheal ectopic thyroid (ITET) is a rare disease, with limited cases reported in the literature. ITET is an unusual congenital abnormality and can be easily mistaken for a respiratory illness. We present a case of a 61-year-old man with a history of slight discontinuous hemoptysis for 2 years. A tracheal mass, which appeared to be connected to the left thyroid gland, was found by chest computed tomography scan. Ultrasound revealed one suspiciously malignant, solid and hypoechoic nodule in the left thyroid gland. After the thyroid origin of the mass was confirmed by bronchoscopic biopsy, the patient underwent segmental resection and anastomosis of the trachea, together with left thyroidectomy. Histopathology of the tracheal tumor showed adenomatous hyperplastic ITET, and the orthotopic left thyroid gland showed nodular goiter with atypical adenomatous hyperplasia. Clinical suspicion is warranted in patients presenting with a tracheal tumor seemingly connected to the thyroid gland, particularly in patients who have imaging features suggestive of a malignant tumor in the orthotopic thyroid but without confirmative histopathology of malignancy before surgery.